Data on the largest specimens of Testudo graeca ibera Pallas, 1814 found in Bulgaria with five new records - Emanuil Mitrevichin; Lidia Sakelarieva; Ivo Ivanchev; Alexander Pulev (Historia naturalis bulgarica, 2023)
Very large specimens of T. graeca ibera were found in Bulgaria, but mostly in the 20th century. Presently, such tortoises are almost absent in the country. Here we summarise data about the largest spur-thighed tortoises registered in Bulgaria and provide information about five new large-sized individuals. We also draw attention to the fact that large specimens can hardly be found in the country today and discuss some possible negative effects of the extinction of these specimens on the existing populations. The maximum straight carapace length of the largest T. graeca ibera ever found in Bulgaria was ≈ 389 mm, but the maximum straight carapace length of the newly measured tortoises was 298 mm. Considering the rarity of such tortoises in the country today, the genes that determine the potential to reach larger sizes may gradually disappear. Thus, the institutions responsible for the conservation of nature should pay attention to areas where the presence of large-sized individuals has been established. This might help preserve the natural genome of T. graeca ibera in the country and therefore the existence of large individuals.